(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The quick progression of technology has suggestively changed the background of communication and interaction, with social media platform developing as a leading forepart in current the social order. These digital platforms have intensely predisposed the activities, attitudes, and insights of individuals, predominantly the adolescence. Social media platform have become crucial to current life, proposing an effective form where people from varied background and places of the world can unite, connect and participate in a uncountable activities. Social media, as a traditional and practical sensation, has altered how society interconnects and constructs its distinctiveness in the digital period